PENERAPAN STRATEGI SEGMENTASI PEMASARAN DALAM PROGRAM TALK SHOW KICK ANDY DAN MATA NAJWA (Lembaga Penerbitan Universitas Esa Unggul, 2020)
The initial step in marketing is market segmentation which is useful for dividing consumers in the market and choosing one of the segments that is the target market. This study aims to find a comparison of marketing segmentation strategies in television talk show programs and find out the similarities, strengths, and weaknesses in implementing marketing segmentation strategies. The research method used is descriptive qualitative, using the main sources namely the Executive Producer of the Mata Najwa talk show program, Mrs. Citra Buana and the Senior Producer of Metro TV, Mr. Daingin Surya Paloh as primary sources and secondary sources in the form of books, internet, and airing talk shows